Analisis Kemampuan Berpikir Kritis dalam Menyelesaikan Soal Cerita di SMP Negeri 14 Mataram - Silvia Rizki Ayu Ningsih; Muhammad Turmuzi; Wahidaturrahmi Wahidaturrahmi; Laila Hayati (Griya Journal of Mathematics Education and Application, 2022)
This study aims to determine students' critical thinking skills in solving story problems in mathematics in class VIII of SMP Negeri 14 Mataram in the 2021/2022 academic year. This type of research uses descriptive qualitative. All students of class VIII are the population, where as many as 32 students were selected using cluster random sampling rules. Data collection uses essay tests to obtain data on critical thinking skills, while interviews are to dig deeper information related to students' critical thinking skills in solving story problems. Based on the results of the study, it was obtained: (1) The students' critical thinking ability in solving story problems in mathematics subjects in class VIII SMP Negeri 14 Mataram in the high category had a percentage of 4.76%. 2) Students' critical thinking skills in solving story problems in mathematics subjects in class VIII SMP Negeri 14 Mataram in the medium category have a percentage of 66.67% 3) Students' critical thinking skills in solving story problems in mathematics subjects in class VIII SMP Negeri 14 Mataram the low category has a percentage of 28.57%.